Imam Balādhuri as a Biographer of Seerah - Qazi, Munir Ahmad; Hashmi, Shah Moen ul Din (Journal of Islamic and Religious Studies, 2017)
Ansāb-ul-Ashrāf is one of the most prominent works of Aḥmad Bin Yaḥya Bin Jābir al- Balādhuri, a muslim historiographer of third Hijri Century. This book is, in fact, a genealogical form of writing history and a primary and authentic source of the Holy biography of the Holy Prophet Muḥammad (ﷺ). This article comprises the life, works and especially the methodology of seerah writing of Balādhuri in his book: Ansāb-ul-Ashrāf. The distinctive characteristics of methodology of seerah writing have been described in this article. He has presented the traditions (Riwayat) about the Seerah of Prophet Muḥammad (ﷺ) in different ways. Sometimes he mentions the whole chain of narrators and sometimes he skips the chain of narrators. The article sheds light on the methodology of seerah writing with special reference to the book Ansāb-ul-Ashrāf.